Qualidade de vida e alterações auditivas em pacientes com anemia falciforme - Arruda, João Sigefredo (2024)
Introduction: Among the genetic changes that affect humans, Sickle Cell Anemia stands out as the most common form in Brazil. In this pathology, red blood cell deformity leads to vaso- occlusive crises that can result in ischemia in the cochlear region, with consequent progressive changes in hearing. Furthermore, these crises generally affect other organs and physiological systems, and occur related to inflammatory processes and crises whose specifications compromise the patients' quality of life. Justification: Considering that there is a growing interest in the scientific community in studying the quality of life associated with chronic pathologies, and because auditory complaints, including tinnitus, are undervalued in hearing assessment, the interest in carrying out this research arose. General Objective: To evaluate the quality of life and hearing changes in patients with Sickle Cell Anemia. Specific Objectives: Identify the main auditory complaints in individuals with Sickle Cell Anemia; Investigate the quality of life in individuals with Sickle Cell Anemia; Characterize the degree and type of hearing loss; evaluate the characteristics of tinnitus auditory complaints in individuals with sickle cell anemia; Verify the association between quality of life and hearing complaints in individuals with Sickle Cell Anemia; Analyze the association between tinnitus and hearing loss in individuals with Sickle Cell Anemia. Method: This is a cross-sectional, comparative and analytical study formed by two groups: Case Group (G1) and Control Group (G2). G1 is made up of patients from the Hematology Outpatient Clinic of the University Hospital of the Federal University of Sergipe. G2 is matched 1:1 by sex and age with G1. In total, 212 participants were admitted to the study, 106 from each group. All subjects responded to the Speech Therapy Anamnesis and underwent Meatoscopy and tonal and Vocal Audiometry. Analyzes were carried out between G1-G2, and in G1 between patients with and without hearing loss. Furthermore, G1 responded to the Visual Analogue Scale to classify the degree of pain; patients who agreed to respond to the WHOQOL-BREF, an instrument that measures quality of life; and whoever mentioned tinnitus responded to the Tinnitus Handicap Inventory. All data were subjected to statistical treatment using the R programming environment (version 4.2.3). Results: We found 34.9% of hearing loss in G1 with a predominance of mild, bilateral sensorineural hearing loss, corroborating the findings in the literature; G1 presented higher proportions of hearing loss compared to G2; G1 had a significant Odds Ratio for having hearing loss; there was a direct and significant correlation between having hearing complaints and the presence of hearing loss in G1. The auditory complaints mentioned were: difficulty understanding speech, tinnitus and hypoacusis. Tinnitus presented bilateral predominance in G1 and G2, with Grade II in G1 and Grade I in G2. Regarding the assessment of quality of life, the WHOQOL-BREF scores, in isolation, suggest that the patients evaluated had a favorable perception in relation to their quality of life. Through Regression Analysis, there was no isolated or independent significant influence, indicating that hearing loss has an effect on quality of life.